Contribution of rare and predicted pathogenic gene variants to childhood-onset lupus: a large, genetic panel analysis of British and French cohorts. (February 2020) - Belot, Alexandre; Rice, Gillian I; Omarjee, Sulliman Ommar; Rouchon, Quentin; Smith, Eve M D; Moreews, Marion; Tusseau, Maud; Frachette, Cécile; Bournhonesque, Raphael; Thielens, Nicole; Gaboriaud, Christine; Rouvet, Isabelle; et al.
Summary: Background: Systemic lupus erythematosus (SLE) is a rare immunological disorder and genetic factors are considered important in its causation. Monogenic lupus has been associated with around 30 genotypes in humans and 60 in mice, while genome-wide association studies have identified more than 90 risk loci. We aimed to analyse the contribution of rare and predicted pathogenic gene variants in a population of unselected cases of childhood-onset SLE. Methods: For this genetic panel analysis we designed a next-generation sequencing panel comprising 147 genes, including all known lupus-causing genes in humans, and potentially lupus-causing genes identified through GWAS and animal models. We screened 117 probands fulfilling American College of Rheumatology (ACR) criteria for SLE, ascertained through British and French cohorts of childhood-onset SLE, and compared these data with those of 791 ethnically matched controls from the 1000 Genomes Project and 574 controls from the FREX Consortium. Findings: After filtering, mendelian genotypes were confirmed in eight probands, involving variants in C1QA, C1QC, C2, DNASE1L3, and IKZF1 . Seven additional patients carried heterozygous variants in complement or type I interferon-associated autosomal recessive genes, with decreased concentrations of the encoded proteins C3 and C9 recorded in two patients. Rare variants that were predicted to be damaging were significantly enriched in the childhood-onset SLE cohort compared with controls; 25% of SLE probands versus 5% of controls were identified to harbour at least one rare, predicted damaging variant (p=2·98 × 10 −11 ). Inborn errors of immunity were estimated to account for 7% of cases of childhood-onset SLE, with defects in innate immunity representing the main monogenic contribution. Interpretation: An accumulation of rare variants that are predicted to be damaging in SLE-associated genes might contribute to disease expression and clinical heterogeneity. Funding: European Research Council.